"A predictive model of building initial trust in sharing economy: MULTI-DIMENSIONAL analysis of facebook users in Morocco". (November 2022) - Aityoussef, Asmaa; Belhcen, Lhacen
Abstract: The present paper aims to identify factors that influence Moroccan's initial trusting intention towards the sharing economy platforms by developing a predictive model of consumer building initial trusting intention towards platforms and providers. Using a triangulation method, the research is based on exploratory studies conducted to gain further insight into the sharing economy in the Moroccan context from platforms and providers' standpoints. Exploratory studies have provided background information to develop a predictive model of building initial trusting intention towards the sharing economy platforms based on McKnight and colleagues' model of building initial trust. A survey questionnaire was used to obtain empirical data from a sample of 238 members of sharing economy Facebook pages. Structural equation modeling was employed to examine 11 hypotheses related to the relationship that exists between predictors and consumers' initial trusting intention toward the sharing economy platforms. Findings provide evidence that Moroccan consumers' initial trusting intention towards these platforms results from specific factors: consumers' personal factors (propensity to trust), knowledge-based trust (consumers' past experience), and external factors (e-worth of mouth). Results highlight the role of consumers' belief in parties' trustworthiness in building initial trusting intention: platform's reliability, functionality, and helpfulness, and providers' competence, benevolence, and integrity. Findings have not shown any influence of perceived risk in developing initial trusting intention. Research has academic and managerial implications. Highlights: Building initial trust towards sharing economy platforms is related to consumers' personality as regards their propensity to trust people and technology. Initial trusting intention is reached through consumers' belief in platforms' reliability, functionality, and helpfulness and in providers' competence, benevolence, and integrity. E-Word of mouth enhances building initial trusting intention towards sharing economy platforms. Consumers' online experiences predict users' intent to trust sharing economy platforms.